"What are my options?": Physicians as ontological decision architects in surgical informed consent. (1st August 2022) - Chen, Stacy S.; Das, Sunit
Abstract: The aim of a theoretically ideal process of informed consent is to promote the autonomy of the patient and to limit unethical physician paternalism. However, in practice, the nature of the medical profession requires physicians to act as ontological decision architects—based on the medical knowledge that they acquire through their experience and training, physicians ontologically determine a subset of viable courses of action for their patient. What is observed is not an unethical physician limitation or biasing of the patient towards certain treatment options that violates patient autonomy or consciously undermines informed consent, but rather a more foundational paternalism that is necessarily inherent to the physician–patient relationship. In this article we argue for a recognition of this underlying physician paternalism and posit that this necessary paternalism is not a foil to patient autonomy, but rather a foundational aspect of the duties of the medical professional within the physician–patient relationship.